EFEKTIFITAS MODEL PEMBELAJARAN TIPE NHT DALAM MENINGKATKAN DAYA INGAT DAN HASIL BELAJAR SISWA - Dian Fitriani Lubis; Mashudi Mashudi; Khosmas Khosmas (ICoTE Proceedings, 2019)
Measure efficacy of achiving educational goals depends upon how the process of learning experienced by student. The problem in this research is  (1) how large the effect of the application of learning model  Number Heads Together to recall the material in learning accounting (2) How large the effect of the application of learning model number head togheter in improving student learning outcomes   (3)How big the influence of the application of learning models number head together in improving the recall material and student learning outcomes in learning accounting . This research took place ion two cycle. Collection tecnique is test and observation.The result is in first cycle indicates that the percentage increase in power remember material in learning accounting achive 71,87 % and the second cycle indicates that the percentage increase in material in learning accouting achive 77,42%. Research result student learning in fisrt cycle is equal to 70,27 with an average of 80. In the second cycle in increased to 89,19 % with the average 83.